2016
DOI: 10.18632/oncotarget.11927
|View full text |Cite
|
Sign up to set email alerts
|

A vicious cycle between acid sensing and survival signaling in myeloma cells: acid-induced epigenetic alteration

Abstract: Myeloma (MM) cells and osteoclasts are mutually interacted to enhance MM growth while creating acidic bone lesions. Here, we explored acid sensing of MM cells and its role in MM cell response to acidic conditions. Acidic conditions activated the PI3K-Akt signaling in MM cells while upregulating the pH sensor transient receptor potential cation channel subfamily V member 1 (TRPV1) in a manner inhibitable by PI3K inhibition. The acid-activated PI3K-Akt signaling facilitated the nuclear localization of the transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 50 publications
(40 reference statements)
0
11
0
Order By: Relevance
“…MM cells and OCs mutually interact with each other to enhance MM tumour growth while developing osteoclastic bone lesions (Abe et al , , ; Yaccoby et al , , ; Ge et al , ). The MM‐OC interactions in bone lesions in MM appear to create a highly acidic milieu due to protons released by OCs and lactate by proliferating glycolytic MM cells (Nakano et al , , ; Amachi et al , ). Acidic microenvironments are generally accepted to confer drug resistance and immune evasion capability in cancers (Kato et al , ).…”
mentioning
confidence: 99%
“…MM cells and OCs mutually interact with each other to enhance MM tumour growth while developing osteoclastic bone lesions (Abe et al , , ; Yaccoby et al , , ; Ge et al , ). The MM‐OC interactions in bone lesions in MM appear to create a highly acidic milieu due to protons released by OCs and lactate by proliferating glycolytic MM cells (Nakano et al , , ; Amachi et al , ). Acidic microenvironments are generally accepted to confer drug resistance and immune evasion capability in cancers (Kato et al , ).…”
mentioning
confidence: 99%
“…Lactic acid, the metabolic end product of anaerobic glycolysis, accumulates along with CO 2 , leading to acidification of the extracellular environment. In subcutaneous xenograft model of solid tumors, the average pH inside MM tumors was ~6.9 compared to pH of 7.4 outside of the tumors ( 85 ). It is the buildup of these acidic byproducts that necessitates activation of various acid/base regulatory salvage pathways within the cells, else the enzymes will be inactivated.…”
Section: Acid/base Regulationmentioning
confidence: 99%
“…In osteolytic bone lesions in MM, therefore, the MM cell-OC interaction appears to create a highly acidic milieu by protons produced by OCs and lactate by proliferating glycolytic MM cells. We reported that acid activates the PI3K-Akt signaling to upregulate the acid sensor TRPV1 in MM cells, thereby forming a positive feedback loop between acid sensing and the PI3K-Akt survival signaling [86]. In addition, tumor acidity has been demonstrated to blunt cytotoxic effects of various chemotherapeutic agents as well as the activity of immune effecter cells [87,88].…”
Section: Targeting Of Osteoclastogenesis and Acidic Microenvironmentsmentioning
confidence: 99%